The Influence of Gender on the Performance of Village-Owned Enterprises in the Province of East Java, Indonesia - Nugroho, Tri Wahyu (HABITAT, 2024)
Village-owned enterprises constitute a significant facet of the government's endeavours to bolster rural economic growth; however, the current scenario in Indonesia showcases a concerning trend of underperformance within these enterprises. This study delves into the impact of female managers on the performance of village-owned enterprises, employing cross-sectional data sourced from 100 such enterprises in East Java, Indonesia. The data was subjected to analysis through an ordered probit model. The principal finding of this study underscores the noteworthy and statistically significant influence exerted by female managers on the performance of village-owned enterprises. This observation implies that enterprises led by female managers tend to exhibit superior performance compared to those managed by their male counterparts. Concurrently, the study underscores the pivotal role of demographic profiles, such as age and education, in shaping managerial performance. These findings carry significant implications for policy formulation. They underscore the urgent need to enhance women's empowerment in rural areas, specifically by encouraging their active participation in village-owned enterprises. Additionally, the study underscores the broader importance of augmenting the knowledge and skills of both male and female managers. Such efforts hold the potential to substantially enhance the contributions of village-owned enterprises to Indonesia's economic landscape. In summary, the study's findings emphasize the pivotal role of female managers in boosting the performance of village-owned enterprises. These insights underscore the necessity of empowering women in rural settings and cultivating knowledge across genders. By addressing these imperatives, policymakers can harness the potential of village-owned enterprises for driving sustainable rural economic development in Indonesia.